Adjustable nanofibers self-assembled from an irregular conformational peptide amphiphile. Issue 4 (5th November 2014) - Qin, Si-Yong; Jiang, Hua-Fang; Peng, Meng-Yun; Lei, Qi; Zhuo, Ren-Xi; Zhang, Xian-Zheng
Abstract : A peptide amphiphile adopting an irregular conformation self-assembled into dendritic nanofibers, peacock-feather-like nanofibers, and even parallel nanofibers. Abstract : A novel peptide amphiphile was elegantly designed to adopt an irregular secondary structure. The peptide could self-assemble into dendritic nanofibers and further yield the peacock-feather-like nanofibers with the deposition of inorganic materials on the dendritic fibers. Triggered by the pH change, the dendritic nanofibers underwent a drastic morphological change and rearranged into parallel nanofibers.